2021
DOI: 10.24297/jssr.v17i.9112
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the quality of life and psychological symptoms of university students in Cyprus during the Covid-19 pandemic

Abstract: The onset of the infectious disease Covid19 originating in Wuhan, China, took over the world in December 2019 and was declared a pandemic in January 2020.  Empirical evidence resulting from relevant research illustrated that the effects of the pandemic itself but also of the strict measures to contain the spread of the virus on the mental health and well-being of affected populations were just as unanticipated as the pandemic itself. Data led to the identification of six idioms of distress: (1) Demoralization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The government must put in place policies that will help businesses thrive even during the pandemic. Further, evidence has shown that COVID-19 has negatively contributed to mental health challenges among different populations[116]-[121]. A previous study in Zambia reported that students experienced mental health challenges due to the COVID-19 pandemic[122].…”
mentioning
confidence: 99%
“…The government must put in place policies that will help businesses thrive even during the pandemic. Further, evidence has shown that COVID-19 has negatively contributed to mental health challenges among different populations[116]-[121]. A previous study in Zambia reported that students experienced mental health challenges due to the COVID-19 pandemic[122].…”
mentioning
confidence: 99%
“…In the constructivist learning model, the leader of the classroom changes from the teacher to the student. Teachers only organize and guide students' training, and through the constructivist learning theory, on the basis of the original teaching and training, they simplify the complex piano training knowledge, and provide students with a knowledge framework that is easy to understand, which can give full play to students' active creativity and construct students' meaning framework for piano training [16]. Teachers can also create a real situation and discuss examples of questions, and improve students' learning efficiency by a level through the scaffolding effect.…”
Section: Design Of Piano Training Based On Constructivism Theorymentioning
confidence: 99%